Yushania doupengshanensis (Poaceae, Bambusoideae), a new bamboo species from south Guizhou, China - Zhang, You-Yuan; Xia, Nian-He (Phytotaxa, 2021)
Yushania doupengshanensis Y.Y. Zhang et N.H. Xia, a new species of the temperate woody bamboo tribe Arundinarieae (Poaceae: Bambusoideae), is described and illustrated from south Guizhou, China. Yushania doupengshanensis is characterised by long-necked rhizomes, usually a single branch at each branching node, densely white puberulous and thin white powdery internodes, tardily deciduous culm sheaths, densely ciliate culm-sheath margins, 6‒12 leaves per ultimate branch, densely puberulous and 8‒9 mm long pseudopetioles. Based on the morphological features, this new species is assigned to section Yushania.